An Improve ACE Algorithm Based on EMD and Cycle Remove - Liang, Wu; Yuanqing, Zhao (Energy procedia, 2011)
This paper introduce EMD as a useful measurement of success in selection of the LDPC code from selected ensemble. When EMD metric associated bad with other cycles in the code graph, which is unavoidable in constructing LDPC codes, we introduce cycle remove in order to improve LDPC codes’ performance. Experimental results show that the algorithm lower error floor and improve LDPC codes’ performance.